2021
DOI: 10.1002/chem.202101662
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Photoreleasers with Fluorescent Reporting

Abstract: Scheme 1. Some of the beneficial and detrimental effects of NO depending on its concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Therefore, NO donors with precise spatiotemporal control of NO release are highly desirable to realize the full potential of NO [ 27 , 28 ]. To this end, light-activatable NO donors, namely NO photodonors (NOPD), are very appealing due to the superb spatiotemporal control light trigger offers [ 29 , 30 , 31 , 32 , 33 ]. Only in recent years the combination of NOPD with conventional chemotherapeutics has been reported [ 34 , 35 , 36 , 37 ], highlighting the double role of photo-released NO as a cytotoxic agent [ 34 ] and inhibitor of the cellular efflux pumps [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NO donors with precise spatiotemporal control of NO release are highly desirable to realize the full potential of NO [ 27 , 28 ]. To this end, light-activatable NO donors, namely NO photodonors (NOPD), are very appealing due to the superb spatiotemporal control light trigger offers [ 29 , 30 , 31 , 32 , 33 ]. Only in recent years the combination of NOPD with conventional chemotherapeutics has been reported [ 34 , 35 , 36 , 37 ], highlighting the double role of photo-released NO as a cytotoxic agent [ 34 ] and inhibitor of the cellular efflux pumps [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies ( 20 22 ) have shown that vascular endothelial function is closely related to the dynamic levels of NO and ET-1, where ET-1 acts on ETA receptors in smooth muscle cells to promote calcium ion release and enhance extracellular calcium ion inward flow, resulting in strong vasoconstriction, which leads to an increase in SVR. NO is an important vasodilator with the opposite effect of ET-1, which is widely distributed in the body and can modulate vascular tone, inhibit platelet monthly endothelial adhesion and thrombosis to prevent vascular endothelial disorders and atherosclerosis ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s, a considerable effort has been dedicated both to the development of novel photoactivatable chemical probes and their applications in various experimental studies. Regarding the scope of PPG applications, the caged substrate could be as Encyclopedia 2022, 2 1227 simple as a proton or an inorganic species or ion (e.g., Ca 2+ [15], Zn 2+ [16], CO [17], NO [18], H 2 S [19]), it could be a small molecule (e.g., second messenger (such as inositol-1,4,5-triphosphate (IP 3 ) [20]), neurotransmitter (notably GABA and glutamate [21,22]), nucleotide [23], peptide [24], drug molecule [25] (such as antibiotics [26], analgesics [27] or anticancer agents [28]) or a more complex biomolecule (e.g., enzymes [29], RNA [30] or DNA [31]) (Figure 3).…”
Section: The Substrate Scope Of Ppgsmentioning
confidence: 99%
“…Since the 1970s, a considerable effort has been dedicated both to the development of novel photoactivatable chemical probes and their applications in various experimental studies. Regarding the scope of PPG applications, the caged substrate could be as simple as a proton or an inorganic species or ion (e.g., Ca 2+ [15], Zn 2+ [16], CO [17], NO [18], H2S [19]), it could be a small molecule (e.g., second messenger (such as inositol-1,4,5-triphosphate (IP3) [20]), neurotransmitter (notably GABA and glutamate [21,22]), nucleotide [23], peptide [24], drug molecule [25] (such as antibiotics [26], analgesics [27] or anticancer agents [28]) or a more complex biomolecule (e.g., enzymes [29], RNA [30] or DNA [31]) (Figure 3). Examples of PPG applications for small molecules/inorganic species: (A) calcium caging with photoactivatable EGTA [32], (B) neurotransmitter glutamate caging with MNI [21], (C) caging the anticancer agent vemurafenib with a nitrobenzyl PPG [33], (D) a coumarin PPG-caged antibiotic agent [34], (E) a coumarin PPG-caged analgesic [27].…”
Section: The Substrate Scope Of Ppgsmentioning
confidence: 99%